The Feasibility of A Science Literacy Assessment Instrument Based on Bengkulu Local Wisdom for Elementary School Students - Tarmizi, Pebrian; Supriatna, Irfan; Izzania, Rizqa Dwi Shofiya Maghfira; Yusnia, Yusnia; Agusdianita, Neza (Program Studi PGMI, 2026)
This study evaluates the theoretical and empirical feasibility of a science literacy assessment instrument integrated with Bengkulu’s local wisdom, Rimbo Larangan, for elementary students. Using the R&D approach with the ADDIE model, the instrument was designed to align scientific literacy dimensions (context, competence, knowledge, and attitude) with local ecological values. Data were collected via expert validation and trials with 30 students, then analyzed using Aiken’s V and descriptive statistics. Results show high theoretical feasibility with an Aiken’s V index of 0.88 and inter-rater reliability of 0.87. Empirically, the instrument demonstrated high reliability (Cronbach’s Alpha 0.89) and valid item distribution across varying difficulty levels. Analysis of student profiles revealed that while the local context significantly boosted scientific attitudes (78%), scientific competence (58%) remains a challenge, particularly in evidence-based reasoning. This study concludes that the Rimbo Larangan-based instrument is a feasible and valid tool for measuring science literacy contextually. It bridges the gap between school science and indigenous ecological knowledge, fostering both environmental awareness and critical thinking in elementary education.